Efektivitas Aromaterapi Citrus Limon dalam Mengurangi Mual, Muntah, dan Kecemasan pada Ibu Hamil Trimester 1 - Nurfajriah Zubair; Fatmah Zakaria; Sri Mulyaningsih; Efri Leny Rauf (Pusat Kajian dan Pengelola Jurnal FKM UMI, 2026)
Nausea occurs due to increased estrogen and human chorionic gonadotropin (HCG) levels in the blood, which trigger vomiting. The psychological effects of estrogen may originate from the central nervous system, resulting in gastric emptying. One way to manage nausea and vomiting and reduce anxiety levels is through non-pharmacological therapy, namely lemon aromatherapy. The purpose of this study was to determine the effect of lemon aromatherapy (lemon citrus) in reducing nausea and vomiting and reducing anxiety levels in pregnant women using a diffuser or vaporizing essential oils through an electric steam tube. The research method used is Quasi Experiment through One Group Pre Test and Post Test approach with a sample of 30 pregnant women in the first trimester. The results of the study using the Wilcoxon Signed Rank Test showed changes in the intensity of nausea and vomiting using the PUQE score experienced a decrease in the Pre Test Mean value of 7.27 to the Post Test Mean value of 6.30 with a p value of 0.01, at the level of anxiety using the DASS21 score the Pre Test Mean value of 9.63 decreased to the Post Test Mean value of 7.67 with a p value of 0.001. Based on the statistical test, it can be concluded that lemon aromatherapy has an effect on reducing the intensity of nausea and vomiting and anxiety levels in pregnant women.